BENEFITS OF RACE RUNNING / PETRA SPORT FOR THE QUALITY OF LIFE OF PEOPLE WITH CEREBRAL PALSY (Fiep Bulletin - online, 2019)
The practice of sports has always been associated with longevity due to physical well-being, but there is currently aninvestment in research that reveals its importance to the quality of life of individuals. Regarding people with disabilities, especiallywith Cerebral Palsy (CP), Petra / Race Running is a sport modality in which the patient is able to take parto in a race running on hisown feet, which seems to be able to provide life satisfaction feeling. The aim of this study is to present a bibliographical review inorder to better understand the contributions of Petra / Race Running to the quality of life of people with Cerebral Palsy. The resultspoint to an increase in the sense of well-being and autonomy, which can be considered a strategy of intervention for the referredpopulation.
Keywords: Adapted Sport; Petra; Race Running; Cerebral Palsy